HUBUNGAN STATUS GIZI (IMT) DENGAN KONSUMSI OKSIGEN MAKSIMAL (VO2 MAKS) SANTRI PONDOK PESANTREN AMANATUL UMMAH SURABAYA - Amalia, Nur Ilma; Kartini, Yanis; Amin, Nur (Sekolah Tinggi Ilmu Kesehatan Holistik, 2018)
Background: Nutrition problems overweight and weight less associated with decreased ability of the body both physical and mental, decreased ability to think, increased risk of pain, and slowing the healing process of disease. One form of decreased physical ability can be seen from the low stamina of a person, stamina is determined by VO2 max, VO2 max is the maximal oxygen uptake or maximal oxygen volume utilized in the exercise until the occurrence of fatigue. Objective: This study aims to determine the relationship of nutritional status with VO2 max of student of Amanatul Ummah Islamic Boarding School, Surabaya. Method: The method used in this research is analytic survey research method with cross sectional approach. The population in this study is all students of class 11 Madrasah Aliyah MBI class in Amanatul Ummah Islamic Boarding School, Surabaya as many as 24 students with 20 samples and taken by using Purposive sampling. Independent variable Nutritional status was measured using BMI calculation and max dependent variable VO2 was measured using multistage step test. Results: The result showed that students in Amanatul Ummah Islamic Boarding School, Surabaya mostly (55%) have normal nutritional status, the students in Amanatul Ummah Islamic Boarding School, Surabaya almost half (45%) have very low VO2 max. The result of statistical test showed that there was no correlation between the nutritional status with VO2 max of students of Amanatul Ummah Islamic Boarding School, Surabaya p = 0,200 (p> 0,05). Conclusion: The conclusion of the research is students in Amanatul Ummah Islamic Boarding School, Surabaya mostly have normal nutritional status. Students in Amanatul Ummah Islamic Boarding School, Surabaya some of them have VO2 max value is very less. There is no correlation between the relationship of nutritional status on VO2 max of Amanatul Ummah Islamic Boarding School, Surabaya.